2020
DOI: 10.21873/anticanres.14293
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Myoferlin Suppresses Migration and Invasion in Clear-Cell Renal-Cell Carcinoma

Abstract: Background/Aim: Myoferlin (MYOF) has emerged as an oncogenic protein in various human cancer types. This study was conducted to investigate comprehensively the expression and functional properties of MYOF in clear-cell renal-cell carcinoma (ccRCC) with respect to its value as diagnostic biomarker and therapeutic target. Materials and Methods: mRNA and protein expression of MYOF were assessed by quantitative polymerase chain reaction and immunohistochemistry. siRNA-mediated knockdown of MYOF was performed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…To investigate the function of MYOF in NPC metastasis, we knocked down MYOF in high metastatic 5-8F cells. Consistent with a previous study in breast cancer cells (Turtoi et al, 2013) and Clear-Cell Renal-Cell Carcinoma (Cox et al, 2020), MYOF knockdown markedly in vitro inhibit cell proliferation, migration and invasion. Indeed, previous studies demonstrated that MYOF depletion reduced tumor development in a xenograft model of human breast cancer (Turtoi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…To investigate the function of MYOF in NPC metastasis, we knocked down MYOF in high metastatic 5-8F cells. Consistent with a previous study in breast cancer cells (Turtoi et al, 2013) and Clear-Cell Renal-Cell Carcinoma (Cox et al, 2020), MYOF knockdown markedly in vitro inhibit cell proliferation, migration and invasion. Indeed, previous studies demonstrated that MYOF depletion reduced tumor development in a xenograft model of human breast cancer (Turtoi et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, high MYOF expression distinguishes a cohort of patient PDA tumours that predict worse overall survival. Several other cancers also show elevated MYOF expression [47][48][49][50] however a role for MYOF in regulation of lysosome function in these cancers remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, overexpression of myoferlin on mRNA and protein level with influence on carcinogenesis has been found in ccRCC, breast cancer, lung cancer and pancreatic adenocarcinoma. [4][5][6][7][8] The expression level of the long non-coding RNA, Fer1L4, has been reported to be either increased or decreased depending on the tumor entity due to oncogenic or suppressive properties. In ccRCC, overexpression of Fer1L4 is associated with shortened survival, whereas lower expression levels were found in gastric and colon cancer leading to poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, altered expression patterns of some ferlin family members have thus been found in several tumor entities. For instance, overexpression of myoferlin on mRNA and protein level with influence on carcinogenesis has been found in ccRCC, breast cancer, lung cancer and pancreatic adenocarcinoma 4–8 . The expression level of the long non‐coding RNA, Fer1L4 , has been reported to be either increased or decreased depending on the tumor entity due to oncogenic or suppressive properties.…”
Section: Introductionmentioning
confidence: 99%